Garroni and Architecture - Ricci, Maurizio (Aesthetica Preprint, 2022)
Emilio Garroni (Rome, 1925-2005) was one of the main philosophers of the twentieth century, publishing volumes and essays that have profoundly influenced the contemporary aesthetic and semiotic debate, not only in Italy. Through an examination of his writings – one of which unpublished – this paper emphasizes the importance and role that architecture played, as an exemplary referent, in the critical path of the great philosopher.